IMPROVING THE TECHNOLOGY TRANSFER AND DIGITALIZATION OF THE AGRICULTURAL ECONOMY - Ukolova, Nadezhda; Monakhov, Sergey; Shikhanova, Juliya; Pototskaya, Lyudmila; Novikova, Nadezhda (Revista Inclusiones, 2020)
In the article, the authors analyze the main directions of agricultural development based on the use of digital technologies. Indicators of the development of digital agriculture in Russia are being presented. The influence of technology transfer on agricultural development is being considered. The scientific basis for the development of technology transfer in the digital transformation of agriculture and the digitalization of the agricultural economy is being disclosed. The practical aspects of the use of digital technologies and their transfer in agriculture are being analyzed. The conclusion is drawn on the need for the active development and improvement of the technology transfer mechanism in modern agriculture, as well as the creation of competitive agricultural production, which uses “highly intelligent” agriculture and smart technologies as its basis.